2012
DOI: 10.1021/ic302045m
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Redox Synthesis of the Charge Transfer Material TTF4[SVMo11O40]

Abstract: The charge-transfer material TTF-SV(IV)Mo(11)O(40) (TTF = tetrathiafulvalene) was prepared by a spontaneous redox reaction between TTF and the vanadium-substituted polyoxometalate (n-Bu(4)N)(3)[SV(V)Mo(11)O(40)] in both solution and solid state phases. Single crystal X-ray diffraction gave the stoichiometry TTF(4)[SVMo(11)O(40)]·2H(2)O·2CH(2)Cl(2), with the single V atom positionally disordered with eight Mo atoms over the whole α-Keggin polyanion [SVMo(11)O(40)](4-). Raman spectra support the 1+ charge assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…In contrast to TTF-A, however, the bond lengths of the corresponding CC and C−S bonds for TTF-B are 1.347(3) Å (C111−C112) and 1.757 Å, respectively. On the basis of structural data, the charge-sensitive central CC bond lengths of the TTF cores [1.318(3) Å for TTF-A and 1.347(3) Å for TTF-B] are within the range of distances of neutral TTF molecules 11,25 and are far from the bond lengths of its radical cation (1.38−1.40 Å). 26 This result suggests that, in the solid state, steric effects in the dimer bring about a longer CC bond length and a shorter C−S bond length, instead of a radical state in TTF-B.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast to TTF-A, however, the bond lengths of the corresponding CC and C−S bonds for TTF-B are 1.347(3) Å (C111−C112) and 1.757 Å, respectively. On the basis of structural data, the charge-sensitive central CC bond lengths of the TTF cores [1.318(3) Å for TTF-A and 1.347(3) Å for TTF-B] are within the range of distances of neutral TTF molecules 11,25 and are far from the bond lengths of its radical cation (1.38−1.40 Å). 26 This result suggests that, in the solid state, steric effects in the dimer bring about a longer CC bond length and a shorter C−S bond length, instead of a radical state in TTF-B.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus E m (1) ¼ À74 mV and E m (2) ¼ 311 mV vs. Fc 0/+ , respectively, so that these two processes are separated by E m (1) À E m (2) ¼ 385 mV. [22][23][24][25] From Fig. 1, it is apparent on the basis of the magnitudes of the relevant limiting, or peak, current values that the diffusion coefficient (D) for TTF is larger than that of TTF + c and TTF 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic susceptibility measurements were made with sample masses of ∼30 mg using a Quantum Design Model MPMS 5 SQUID magnetometer in dc magnetic fields of 0.01, 0.10, and 1.0 T. Diamagnetic and other corrections were made as described previously using Pascal’s constants and other published data as applicable. , …”
Section: Methodsmentioning
confidence: 99%
“…However, in principle, if the thermodynamics associated with reduction of POM anions can be set up appropriately, TTF-POM materials should become available by spontaneous reaction of TTF and POM, analogously to the reaction between TTF and TCNQ. This was achieved recently in the reaction of TTF and ( n -Bu 4 N) 3 [SVMo 11 O 40 ] . In this paper, it is now shown that the vanadium-substituted Keggin-type polyoxometalate ( n -Bu 4 N) 3 [SVW 11 O 40 ], synthesized by vanadium substitution in the parent ( n -Bu 4 N) 2 [SW 12 O 40 ] POM provides access to a V V/IV reduction process that has a more positive potential than that for the TTF 0/+ oxidation.…”
Section: Introductionmentioning
confidence: 91%